UPAYA MENINGKATKAN KETERAMPILAN MENULIS KARANGAN NARASI MELALUI MEDIA GAMBAR SERI PADA SISWA KELAS V MADRASAH IBTIDAIYAH SIS ALJUFRI TATURA PALU - Saddiah, Saddiah (BAHASANTODEA, 2015)
Abstack The research problem was to develop narrative writing skill of the Fifith Grade at Madrasah Ibtidaiyah Sis Aljufri Tatura Palu and how was the procedure of the application of Narrative Essay Writing Skill through Series Picture of the Fifith Grade at Madrasah Ibtidaiyah Sis Aljufri Tatura Palu. This research aimed to develop students' ability to write narrative essays of the Fifith Grade at Madrasah Ibtidaiyah Sis Aljufri Tatura Palu and applied the pocedure of narrative essay writing through media image series fifth grade students at Government Elementary School Sis Aljufri Palu. Data collected by evaluation sheets, observation sheets, questionnaires, and documentation. Based on the research findings, it showed that the use of series picture media could improve students' writing skills narrative. It was seen an increase in the number of the students who have mastery learning from cycle 1 to cycle 3. In addition, there was an increase in the average value of narrative writing skills from the cycle 1 to cycle 3. In pre-action, the students who have achieved the criteria of succes were 8 students (27%), in the first cycle were 19 students (63%), in the second cycle were 21 students (70%), and the third cycle as many as 23 students (77%). The average of narrative writing skills of students in pre-action activities was 62.50 in the first cycle was 67.33, second cycle was 71, 53 and third cycle was 74.03. Furthermore, the application of contextual teaching and learning in the teaching of writing essays through picture series was developed on observations of narrative writing. In the first cycle, the students’ narrative writing was 70%, the second cycle was 78% and in the third cycle was 90%. Keywords: Writing, Narrative Essay, Picture Series.